2008
DOI: 10.1002/elps.200700466
|View full text |Cite
|
Sign up to set email alerts
|

Development of a capillary electrophoresis‐mass spectrometry method using polymer capillaries for metabolomic analysis of yeast

Abstract: Metabolomics is an emerging field in analytical biochemistry, and the development of such a method for comprehensive and quantitative analysis of organic acids, carbohydrates, and nucleotides is a necessity in the era of functional genomics. When a concentrated yeast extract was analyzed by CE-MS using a successive multiple ionic-polymer layer (SMIL)-coated capillary, the adsorption of the contaminants on the capillary wall caused severe problems such as no elution, band-broadening, and asymmetric peaks. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…27,38 For many biological samples, proteins and peptides adsorbed onto the silica surface during separation reduced the repeatability of measurement. Different coatings have been applied to the inner surface of the capillary to improve the repeatability; 27,39-42 however, they reduced the quality of the nanospray in our experiments. Generally, a number of parameters are associated with a stable spray and a successful CE-MS measurement, including the emitter geometry, interface design, buffer composition, SL flow rate, spray voltage and cleanliness of the interface.…”
Section: Resultsmentioning
confidence: 99%
“…27,38 For many biological samples, proteins and peptides adsorbed onto the silica surface during separation reduced the repeatability of measurement. Different coatings have been applied to the inner surface of the capillary to improve the repeatability; 27,39-42 however, they reduced the quality of the nanospray in our experiments. Generally, a number of parameters are associated with a stable spray and a successful CE-MS measurement, including the emitter geometry, interface design, buffer composition, SL flow rate, spray voltage and cleanliness of the interface.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, Escherichia coli and Saccharomyces cerevisiae have frequently been employed as model microbes [5,6], because these species are biologically well characterized, and it is relatively easy to manipulate their genes. Mechanistic studies have revealed that HP treatment damages cellular organelles, membrane structures, and membrane proteins [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…We assessed the metabolites of the cells restoring the damages after high-pressure treatment using CE/MS methods. We focused on amino acids, since these metabolites often contribute to the homeostasis of cells and can be easily separated from cells (Tanaka et al 2008). The metabolomics analysis suggested the significant accumulation of glycine, valine, isoleucine, leucine, asparagine, aspartic acid, and tyrosine in the cells (Tanaka et al 2010).…”
Section: Proteasome and Its Function Could Be The Crucial Target Of Dmentioning
confidence: 99%
“…Metabolomics is an emerging field in analytical biochemistry, and the development of this field for comprehensive and quantitative analysis of organic acids, carbohydrates, and nucleotides is a necessity in the field of functional genomics (Tanaka et al 2008). We assessed the metabolites of the cells restoring the damages after high-pressure treatment using CE/MS methods.…”
Section: Proteasome and Its Function Could Be The Crucial Target Of Dmentioning
confidence: 99%